STAGES OF DEVELOPMENT OF BUSINESS MODELS IN THE DIGITAL ECONOMY (Marketing Journal, 2025)
This article analyzes the theoretical foundations of digital economy and digital business models, their role in national and global economies, as well as the developing digital infrastructure and business models in Uzbekistan. The significance of informati on and communication technologies (ICT) in the process of digital transformation, digital infrastructure, e -business and trade, digital products and services, as well as the role of big data and artificial intelligence in enhancing economic efficiency are highlighted.
Keywords: digital economy; business models; ICT; traditional business models; digital business models; analysis; digital platform; service and trade processes; sector